Alien Visitation, Extra-Terrestrial Life, and Paranormal Beliefs - Dagnall, Neil; Drinkwater, Kenneth Graham; Parker, Andrew (Journal of Scientific Exploration, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial","sans-serif"; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-fareast-language:EN-US;} --> <!--[endif]--> The present paper investigated the nature and structure of extra-terrestrial beliefs. Respondents completed a booklet containing items measuring belief in extra-terrestrial life, alien visitation, and paranormal belief (Revised Paranormal Belief Scale, R-PBS; and the Australian Sheep Goat Scale, ASGS). Responses were analyzed using principal component analysis (PCA), and a three-factor structure emerged: alien visitation, belief in extra-terrestrial life, and the search for extra-terrestrials. Further analysis revealed that males scored higher than females on belief in extra-terrestrial life and the search for extra-terrestrial life. No difference was observed for alien visitation. Correlational analysis found significant positive associations between each of the extra-terrestrial life factors and alien visitation. In addition to this, the extra-terrestrial life factors and alien visitation were found to correlate with overall paranormal belief (ASGS), and the two factors of the R-PBS (Traditional Paranormal Belief and New Age Philosophy). Alien Visitation was more strongly correlated with the paranormal belief measures than the extra-terrestrial belief factors; these were found to be negatively correlated with the paranormal belief measures when Alien Visitation was controlled for. These findings indicate that only more extreme Alien Visitation beliefs were associated with belief in the paranormal. Keywords: alien visitation—belief in extra-terrestrial life—search for extra-terrestrial life—paranormal belief